Some foods and their adulteration - Fish, Frances Walker (My University, 1905)
Introduction: When people are in a low state of civilization the foods consumed are such as may be found near their homes and are not changed much from in which they are grown. As civilization advances the taste of the people develops and a greater variety of food is demanded. This desire for a variety in diet has led to the great industries which deal with the varied preparations of foods. The spirit of democracy in this age leads everyone to desire all the luxuries which are produced and the manufacturer, in his endeavor to meet this demand, must produce all kinds of articles at low cost When the people want an article at a price below the cost of production the manufacturer is encouraged to substitute cheaper materials and make as good an article as he can to satisfy the demand. When the consumer understands the difference between the two articles this is a commendable business and increases the prosperity of the country. It is a good thing for the people to have a great variety of food stuffs within their reach but the advantage to the consumer is entirely destroyed when the substitution of poorer material is made without his knowledge and he buys an article which is not of the quality he supposes it to be.
Food adulterants
Citation: Fish, Frances Walker. Some foods and their adulteration. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Cause of Adulteration; Prevention of Adulteration; Theses; Manuscripts (documents)